Peripheral blood inflammatory score using a cytokine multiplex assay predicts clinical outcomes in patients treated with atezolizumab-bevacizumab for unresectable HCC - Cho, Hee Sun; Lee, Soon Kyu; Han, Ji Won; Kwon, Jung Hyun; Nam, Soon Woo; Lee, Jaejun; Yang, Keungmo; Sung, Pil Soo; Jang, Jeong Won; Yoon, Seung Kew; Choi, Jong Young (Frontiers in Immunology, 2025)
BackgroundSeveral serum cytokines have been proposed as biomarkers for predicting the outcomes of patients with hepatocellular carcinoma (HCC) receiving tyrosine kinase inhibitors. However, their role in atezolizumab plus bevacizumab (AB) treatment needs to be more elucidated.MethodsWe examined various serum cytokines, including interferon-γ (IFN-γ), interleukin-10 (IL-10), IL-12, IL-17, IL-2, IL-6, and tumor necrosis factor, using a Luminex cytokine multiplex assay before AB treatment in prospectively enrolled 116 AB-treatment patients for the derivation cohort and 54 patients for the external validation cohort. We collected baseline characteristics, including neutrophil-lymphocyte ratio (NLR) and C-reactive protein (CRP) levels, and prospectively observed clinical outcomes.ResultsAmong various peripheral blood inflammatory markers, high NLR, CRP, IL-2, and IL-12 levels were significantly associated with poor progression-free survival (PFS) and overall survival (OS) in patients with AB-treated HCC. Through sensitivity analysis, we defined the high peripheral blood inflammatory score (PBIS) group, which included two or more of the following elevated factors: NLR, CRP, IL-2, and IL-12. The high PBIS group had elevated serum inflammatory cytokines and a higher tumor burden than the low PBIS group. A high PBIS score was an independent risk factor associated with poor OS, PFS, and objective response rate (ORR) in multivariate analyses, which was also confirmed in the validation cohort and propensity score-matched cohort. However, it was not a significant factor for OS, PFS, or ORR in lenvatinib-treated patients.ConclusionThese results suggest that a peripheral blood marker-based scoring system can significantly predict clinical outcomes in patients with AB-treated HCC. This non-invasive biomarker is expected to be a potential predictive and prognostic factor for AB treatment.